ПРОБЛЕМА КОРОЛІВСЬКОЇ ВЛАДИ В ІСТОРИЧНИХ УМОВАХ ФРАНЦІЇ ДРУГОЇ ПОЛОВИНИ XVI СТОЛІТТЯ (Zaporizhzhia Historical Review, 2021)
The author of the article draws attention on history of early modern Europe and on the questions which a new epoch put before society in the field of political life. Among problems which provoked the conflicts of French society there was a problem of power. In the article the author exposes the role of question of power during Civil war, its understanding and perception by different layers of society and historical sources of these problems.